EVALUASI PEMAHAMAN KOGNITIF DIKLAT KEPALA TATA USAHA MADRASAH DI BALAI DIKLAT KEAGAMAAN SEAMARANG - Masfifah, Masfifah (Universitas Negeri Surabaya, 2019)
Semarang Religious Education and Training Center is an institution that serves to educate prospective civil servants or State Civil Apparatuses. Types of education are many kinds, but what the authors mean is the Madrasah Administration Head Training, Seoarang PNS in ASN Management material, which is derived from PP 11 of 2017 said that a PNS at least in one year must have a minimum of 20 hours of Education Training certificate. The author makes and studies more in Madrasa Administration Training, because based on the Pre test result data guided by the homeroom teacher (widyaiswara) and the organizing committee, the results are not in line with the expectations of the Semarang Religious Education Center. The test post is the final destination after participants take part in KTI learning so that the implementation of the education program knows the results of the study, the test post is carried out after the participant receives the learning material in accordance with the curriculum and syllabus. The results of the pre-test and post-test we processed the data through quantitative and descriptive statistical methods, resulting in the finding that participants of the Madrasah Administration Head of Education for the following year had to take part in the training again because it was not in line with the expectations of the Semarang Religious Education Center. The final result is in accordance with the statistical data processing and the writer describes one class of 35 participants, the pre test average score is 59, the results of the post test score 68.